The Role of Financial Digitalization in Achieving Efficient Financial Performance Applied Research into Some Banks Listed on the Iraqi Stock Exchange - Ali, Kareem Hasan; Dahham, Makki Shahad; Yaseen, Jasim Mohammed (Research Parks Publishers, 2024)
The primary objective of the study is to find or study the impact of digital finance, represented by the following dimensions (electronic bank branches, automated teller machines, electronic payment cards, and open banking services), on achieving efficient financial performance (capital adequacy, profitability, credit risk, liquidity) in commercial banks listed on the Iraqi Stock Exchange for the period (2015-2021). In order to achieve the goal of this study, statistical methods models were relied upon, using the least squares method, as the results of the study concluded that the relationship between financial digitalization and the efficiency of financial performance constitutes A positive linear relationship, meaning that the greater the financial digitization, the more efficient the financial performance. The research also presented a set of recommendations that relevant authorities can use.